Litter Decomposition on the Old Parak Ecosystem in Maninjau West Sumatra Indonesia - Kardiman, Reki; Simangunsong, David (Bioscience, 2024)
This study aimed to analyze the rate of litter decomposition on the old parak ecosystem in Maninjau, Tanjung Raya District, Agam Regency, West Sumatra Indonesia. Data were collected at four different vaillages, each was located at one compas point surrounding the Maninjau Lake. The sites were purposively selected according to the zonation of vegetation, where the parak ecosystem appeared between paddy field and forest. Three of 20x20 m plots were established at each location, in which one of 1x1 meter subplot was established in the centre, given 12 subplots in total. All litters within the subplots were collected and measued the wet weight, about 800 grams of the litters were collected, 200 grams of it were dried, while other 600 grams were placed into six litter bags (100 grams each) and placed again at each subplot. Two litter bags were collected each month, dried and analyzed the rate and percentage of decomposition. The results showed that the average litter decomposition rate at parak ecosystem in Maninjau was 0.6 gr/day, and 50% litters were decompossed in 90 days. The rate of decomposition of litter varied between loactions, where the lowest decomposition rate was found at the western part of the Maninjau Lake, especially for leaves litters. This study revealed that a park ecosystem in Maninjau requires six month decompotition to completely change litters into soil, and with about 6.4 tons of litters per hectar, resulting 5 tons of biomass, this provides 5 tons of organic matters for each hectare of parak ecosystem.